2019
DOI: 10.1097/prs.0000000000005652
|View full text |Cite
|
Sign up to set email alerts
|

The Anterolateral Thigh Flap for Achilles Tendon Reconstruction: Functional Outcomes

Abstract: Background: Following Achilles tendon rupture and repair, reruptures or infections are not infrequent. Consequently, several surgical techniques have been described to decrease complication rates. This study aimed to evaluate the outcomes of the free composite fasciocutaneous anterolateral thigh flap including fascia lata for reconstruction of combined complex soft-tissue and Achilles tendon defects. Methods: Within an 8-year period, 34 patients having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
0
24
0
3
Order By: Relevance
“…[30][31][32] There are some unignorable drawbacks including vascular crisis, secondary thinning procedures for bulky flap and deficit of quadriceps femoris muscle contraction forces. 2,31 The radial forearm flap with palmaris longus tendon provides thin and pliable integument and long tendon, while it has significant donorsite morbidity and is better suited for small rather than massive defects. 33,34 Dobke et al 35 reported satisfactory outcomes of the extended temporoparietal fasciagaleal flap for a long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[30][31][32] There are some unignorable drawbacks including vascular crisis, secondary thinning procedures for bulky flap and deficit of quadriceps femoris muscle contraction forces. 2,31 The radial forearm flap with palmaris longus tendon provides thin and pliable integument and long tendon, while it has significant donorsite morbidity and is better suited for small rather than massive defects. 33,34 Dobke et al 35 reported satisfactory outcomes of the extended temporoparietal fasciagaleal flap for a long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Defects of the Achilles tendon and overlying soft tissue are not infrequent, and the reconstruction of the complex defects is still Challenging. 1,2 Bicycle and motorcycle wheel spoke injury often result in the complex defect at the Achilles tendon region, especially in children. 3,4 The Achilles tendon is the most easily ruptured tendon, and surgery is a commended solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ALT flap is mainly harvested as fasciocutaneous free flap incorporating fascia lata (FL), overlying adipose tissue and skin, or as myocutaneous flap with additional muscular component to increase bulk [5][6][7]. The FL as fascial component of the ALT flap is preferred particularly for tendon reconstruction of lower and upper limbs [8,9]. In addition, the FL is routinely used as non-vascularized graft in anterior skull base surgery or rhinology to cover small skull base defects.…”
Section: Introductionmentioning
confidence: 99%
“…1 While some of the defects resulting from such tumor extirpation can be closed by simple, intermediate, or complex repair, a large number result in tissue deficits that require flap reconstruction. [2][3][4][5][6] Flap design depends on a plethora of factors; however, initial surgical planning always needs to ensure proper vascularization and blood supply of the flap. 7 Ultrasound imaging is a commonly used tool to visualize the course of vessels prior to surgery and to facilitate the planning…”
mentioning
confidence: 99%